PENELITIAN TINDAKAN KELAS - Noor Azida Batubara; Dienul Hasanah; Husna Masithoh; Pingkan Sukma; Siti Nurhalimah (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze and compare the ideas of three prominent figures in Classroom Action Research (CAR), namely John W. Creswell, Robert P. Pelton, and Geoffrey E. Mills. Each of these scholars has made significant contributions to the development of CAR methodology, particularly in research design, action procedures, and reflective approaches to improving classroom instructional practices. This study employs a literature review method by examining the primary works and academic references related to each theorist. The findings indicate that Creswell emphasizes a systematic research framework supported by in-depth qualitative analysis; Pelton focuses on practical strategies that empower teachers to conduct action research; while Mills introduces a flexible reflective spiral model oriented toward continuous improvement. Despite their different emphases, all three share a common view of CAR as a means to enhance instructional quality through cycles of action and reflection. This research concludes that integrating the perspectives of these three scholars can produce a comprehensive and applicable CAR model, particularly within the context of Indonesian education.